A sustainable approach for the multi-dimensional exploitation of mixed biochar based nano-composites. (15th March 2023) - Ahmad, Awais; Zahra, Mushkbar; Fakhar e Alam,; Ali, Shafaqat; Pervaiz, Muhammad; Saeed, Zohaib; Younas, Umer; Mushtaq, Muhammad; Rajendran, Saravanan; Luque, Rafael
Highlights: Biochar a ecofriendly material for sustainable energy. Biochar based nanomaterials for production of biofuel and bioenergy. An efficient material for production of biofuel on large scale. Recent advancement and future prospective for bioenergy applications. Abstract: Biochar (BC) has caught attention for being eco-friendly and removing perilous pollutants (PP) from environment; nevertheless, primitive biochar frequently show little adsorption ability. Hence, different alteration technologies in biochar (BC) have been proposed to enhance its removal capacity against hazardous pollutants. Nano-materials and biochar based nano-composites have been exploited as bio-sorbent (for removal of hazardous pollutants from aqueous media) and soil conditioner (for improving soil texture and physiochemical properties) etc. Mixed biochar based nano-composites have fascinated concentration due to their higher competency to remove and degrade the toxic elements. Modification of biochar by metal or non-metal based nano-materials improves the physiochemical properties of pure biochar, increases the functional groups and ultimately provides more active sites on its surface. The current study is aimed for waste management by transforming the agro food and other waste being most abundant and cost-effective into valued product i.e. biochar, its modification to obtain biochar based nano-composites through a sustainable way and their multi-dimensional applications. This paper identified various strategies to produce biochar and biochar-based metal and non-metal nano-composites and their removal efficiency for the toxic elements and mainly focused on the bio-fuel and bio-energy production. Furthermore, factors affecting their efficiency have also been reviewed in this paper.